Illness and the development of Master-Slave relations in Morrison’s A Mercy and Lalami’s The Moor’s Account - al-Sewwi, Esraa; Awad, Yousef (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this paper is to analyze and compare Master-Slave relations in two historical novels by African-American novelist Toni Morrison and Arab-American novelist Laila Lalami. The study aims at examining the formation of Master-Slave relations in Morrison’s A Mercy (2008) and Lalami’s The Moor’s Account (2014), with a particular focus on the role illness and healing play on their development. This will be done within three stages of before, during and after illnesses. Moreover, Hegel’s Master-Slave Dialectic theory will serve as the theoretical framework upon which Master-Slave relations will be examined within their historical and cultural contexts. Masters’ illnesses in both novels represent a turning point in the course of Master-Slave relations, providing Slaves with a chance to prove to themselves and to their Masters that the two are involved in complex and multifaceted connections. However, the study shows that the way illnesses affect the development of the relation in each novel differs drastically. In The Moor’s Account, illness offers an opportunity for Mustafa and his companions to add value to the services they offer to the Native American tribes they serve. In contrast, the emergence of illness in A Mercy negatively affects Lina’s relationship with Rebekka as the latter loses faith in the former and substantially downgrades her efforts and labors. The results of this study reveal the importance of external factors, such as the appearance of illnesses, in defining and affecting Master-Slave relations. Hence, by reading both novels alongside each other, the study highlights sociopolitical, cultural and historical aspects in the two narratives that have not been fully explored previously.